Detection of respiratory viruses in asymptomatic children undergoing allogeneic hematopoietic cell transplantation1. Issue 1 (14th September 2012) - Srinivasan, Ashok; Flynn, Patricia; Gu, Zhengming; Hartford, Christine; Lovins, Richard; Sunkara, Anusha; Srivastava, Deo K.; Leung, Wing; Hayden, Randall T.
Abstract Detection of respiratory viruses by molecular methods, in children without respiratory symptoms undergoing hematopoietic cell transplantation (HCT), has not been well described. A prospective study of 33 asymptomatic children detected respiratory viruses in 8 of 33 (24%) patients before HCT. Human rhinovirus (HRV) was detected in five patients, and human adenovirus (hADV) in three patients. Two additional patients shed HRV, and one shed human coronavirus (hCoV), post‐HCT. Two patients had co‐infections. Of the 11 asymptomatic patients where respiratory virus was detected, 3 (27%) later developed an upper respiratory tract infection, from the same virus. Pediatr Blood Cancer 2013; 60: 149–151. © 2012 Wiley Periodicals, Inc.